COMBINATION OF HYPNOSIS THERAPY AND RANGE OF MOTION EXERCISE ON UPPER-EXTREMITY MUSCLE STRENGTH IN PATIENTS WITH NON-HEMORRAGHIC STROKE - Chandra Irawan; Mardiyono Mardiyono; Suharto Suharto; Aris Santjaka (Belitung Nursing Journal, 2018)
Background: Range of Motion (ROM) exercise has been identified in the literature that it has an effect in improving muscle strength, especially in patients with stroke. However, little is known about the effect of ROM exercise combined with hypnosis therapy. Objective: To determine the effect of combination of hypnosis therapy and ROM exercise on upper extremity muscle strength in patients with non-hemorrhagic. Methods: This study employed a quasi-experiment with pretest-posttest control group design. Thirty-two samples were selected using simple random sampling, which 16 randomly assigned in the experiment and control group. Muscle strength was measured using muscle strength scale. Hypnosis Deepening test was used to measure the level of hypnosis depth. Paired t-test and Independent t-test were used for data analysis. Results: The mean value of muscle strength in the experiment group was 3.50 and the mean value in the control group was 2.62. Independent sample t-test obtained p-value = 0.012, indicated that there was a statistically significant difference in the mean of muscle strength of upper extremity in the experiment and control group. Paired t-test obtained p-value = 0.000, which indicated that there was significant difference between the average of muscle strength value before and after treatment Conclusion: The combination of hypnosis therapy and ROM exercise has a significant effect in increasing muscle strength of upper extremity in patients with stroke non-hemorrhagic.